Irregular migration from Ukraine and Belarus to the EU: A risk analysis study - Marta Jaroszewicz; Marta Kindler (University of Warsaw, Centre of Migration Research (CMR), 2015)
The aim of this paper is to analyse, through the prism of risk theories, irregular migration at the final stage of Eastern European migratory route, i.e., migration of people originating from or transiting through Eastern Europe to the EU. Risks taken by different actors associated with migration along this route have been considered. At the micro-level these are risks borne by irregular migrants themselves. At the mezzo-level these are risks borne by states affected by irregular migration as either transit or end destinations for irregular migrants. And, at the macro-level, these are risks taken by the European Union as the supranational organisation dealing with EU-wide consequences of irregular migration.The concept of risk is the most suitable theoretical approach to be applied in the case of analyzing irregular migration. Irregular migration is regarded by states as a challenge due to its very uncertain nature - states' inability to control it and lack of information on the arriving foreigners. However, Eastern European irregular migration cannot be considered as a security threat. It is very modest both in the numbers and possible adverse consequences for all stakeholders involved. Those most exposed to danger are irregular migrants themselves. A constructionist perspective on risk typical for sociology and international relations differs from the 'traditional' realist approach, used by law enforcement agencies, with risk being perceived as 'real' and a quantifiable phenomenon. The paper attempts to reconcile with each other those both perspectives. The following risk's components have been investigated: failure and its effects; failure likelihoods and modes; failure significance.
Keywords: 330; irregular migration; Eastern Europe; EU; risk analysis